Effect of Traditional Chinese Medicine Combined with Bladder Perfusion with Hydroxycamptothecin on Color Ultrasound and Clinical Efficacy in Patients with Bladder Cancer Surgery - Shisheng Zhou (Hindawi Limited, 2021)
Objective. To observe the clinical effect of Xiaozheng Decoction combined with bladder perfusion with hydroxycamptothecin in the treatment of bladder cancer. Methods. A total of 92 bladder cancer patients admitted to our hospital from January to December 2018 were selected and divided into an observation group and a control group according to the random number table method, with 46 cases in each group. The observation group was given Xiaozheng Decoction combined with bladder perfusion with hydroxycamptothecin, and the control group was given hydroxycamptothecin. The levels of serum-related factors (intercellular adhesion molecule-1 (ICAM-1), E-cadherin, cell adhesion molecules (CAM), fibroblast growth factor (FGF), and vascular endothelial growth factor (VEGF)), white blood cell (WBC) level, immune function indexes, short-term total response rate, and incidence of adverse reactions were compared between the two groups before and after treatment. Results. After 2 years of postoperative treatment, the levels of ICAM-1, E-cadherin, CAM-1, FGF, and VEGF (a, b, c) in both groups were improved compared with those before treatment and the observation group was better than the control group p<0.01. The number of WBCs was significantly higher than in the control group after Traditional Chinese Medicine (TCM) treatment. The observation group was better than the control group in increasing CD3+ and CD4+ levels and decreasing CD8+ level p<0.05, indicating that this prescription could improve the immune function of patients. The recurrence rate in the observation group was 6.52% after 2 years of treatment, lower than 17.39% in the control group. Color ultrasound parameters showed that there were no statistically significant differences in arrive time (AT) and time to peak (TTP) between patients with and without recurrence and peak intensity (PI) and washout time (WT) were higher in patients with recurrence than in patients without recurrence p<0.01. The incidence of adverse reactions was significantly lower than that of the control group p<0.01. Conclusion. The clinical effect of Xiaozheng Decoction combined with hydroxycamptothecin on the treatment of bladder cancer was clear and superior to that of hydroxycamptothecin, which could effectively improve the serological indicators of patients with a low incidence of adverse reactions and prolong the survival cycle of patients. Therefore, it is worthy of promotion and application.